The Influence of Somatic, Audio, Visual Learning Models, Intellectual (SAVI) Rock PhET Against Students' Activities and Learning Outcomes - Elvika Elvika; Widya Herma (Jurnal Pembelajaran Fisika, 2022)
The SAVI learning model combines four learning styles, for example visual (understanding everyday life phenomena through modules), somatic (collecting data), intellectual (solving problems), Auditory (communicating observations in front of the class). The purpose of this study was to determine the effect of the PhET-Assisted Somatic, Audio, Visual, Intellectual Learning Model (SAVI) on Students ' Activities and Learning Outcomes. This study uses a Quasi Experimental Design, the design used is the Nonequivalent Control Group Design . Sampling using probability sampling technique , then, the type used in this study is simple random sampling. So that we get class XI IPA 1 as the experimental class and class XI IPA 2 as the control class. Student activity measured by observation for the two classes experienced a fairly far comparison, the average control class activity was 69.72 while the experimental class was 78.88. For the analysis of student learning outcomes , t count is 3.01, with t table 2.81, which means t count t table , the conclusion is H 0 is rejected and H 1 is accepted which means there is an influence of Somatic, Audio, Visual, Intellectual Learning Models (SAVI) PhET Assisted on Activities and Learning Outcomes. Keywords: SAVI, PhET Simulation , Activity, Learning OutcomesDOI: http://dx.doi.org/10.23960/jpf.v10.n1.202208